Method for manufacturing an aluminum-steel composite cylinder liner
Patent Information
- Application Number
- CN202410357509.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-03-27
AI Technical Summary
但其本体部分与衬套采用卡接方式相连,长期使用后卡接部位容易磨损,从而导致连接松动,影响离合器缸套的稳定性,甚至带来安全隐患
[0023] The above-mentioned method for preparing aluminum-steel composite cylinder liners involves filling a mold cavity adapted to the cylinder liner body with a mixed powder containing silicon carbide-reinforced aluminum-based composite material raw material powder, placing a stainless steel bushing in a mold cavity adapted to the bushing, and pressing it during the forming process. Under the action of extrusion pressure, the mixed powder enters the millimeter pores of the stainless steel bushing to form a tenon-and-mortise structure. Subsequently, during the sintering process, the alloying elements in the mixed powder form a liquid phase and enter the micro-nano pores of the stainless steel bushing, playing an anchoring role. After solution treatment and aging treatment, the resulting aluminum-steel composite cylinder liner has a strong bond between the silicon carbide-reinforced aluminum-based composite cylinder liner body and the stainless steel bushing. The stainless steel bushing ensures the high-temperature resistance of the friction surface, while the aluminum-based composite cylinder liner body ensures advantages such as light weight, high strength, and wear resistance.
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder metallurgy technology, and in particular to a method for preparing aluminum-steel composite cylinder liners. Background Technology
[0002] The clutch cylinder liner is a key component of the clutch system, located between the clutch pressure plate and the driven plate. It transmits pressure from the pressure plate to the driven plate, enabling clutch engagement and disengagement, while simultaneously ensuring stable clutch operation and reducing wear on the friction plates. As a crucial part of the clutch system, the clutch cylinder liner must possess: good wear resistance to withstand friction from the friction plates and pressure plate; excellent thermal conductivity for effective heat dissipation; stable dimensional accuracy to ensure proper fit with other clutch components, thus guaranteeing the normal operation of the clutch system; and superior mechanical strength and rigidity to withstand the pressure and impacts during clutch operation.
[0003] Traditional clutch cylinder liners are mostly forged from alloy steel, which results in a large weight, which is not conducive to increasing transmission speed and has limited power density improvement.
[0004] Silicon carbide-reinforced aluminum matrix composites possess low density, high specific strength and stiffness, high thermal conductivity, and excellent wear resistance and corrosion resistance, making them promising candidates for lightweight structural components. Using silicon carbide-reinforced aluminum matrix composites to manufacture clutch cylinder liners can effectively reduce cylinder liner weight and significantly improve power density; however, its high-temperature resistance is limited, making it unsuitable for manufacturing cylinder liners with higher performance requirements.
[0005] CN214367362U discloses a clutch cylinder liner whose body is made of aluminum alloy, reducing the overall weight of the cylinder liner. The bushing, serving as the friction pair, and the liner bushing, serving as the lining surface, are both made of alloy steel, featuring stable friction coefficient, good anti-adhesion performance, and fast heat conduction. However, the body and bushing are connected by a snap-fit method, which is prone to wear after long-term use, leading to loosening of the connection, affecting the stability of the clutch cylinder liner, and even posing a safety hazard. Summary of the Invention
[0006] Therefore, it is necessary to provide a method for preparing an aluminum-steel composite cylinder liner that enables a tighter connection between the silicon carbide-reinforced aluminum matrix composite cylinder liner body and the stainless steel bushing.
[0007] A method for preparing an aluminum-steel composite cylinder liner includes the following steps:
[0008] Provides silicon carbide reinforced aluminum matrix composite material powder;
[0009] The silicon carbide reinforced aluminum matrix composite material raw material powder is mixed evenly with polyurethane to obtain a mixed powder;
[0010] Provide 2Cr13 martensitic stainless steel bushings with millimeter and micro / nano pores evenly distributed on the surface;
[0011] A pressing mold is provided, the mold having a cavity adapted to the cylinder liner body and a cavity adapted to the bushing;
[0012] The mixed powder is filled into a mold cavity that fits the cylinder liner body, the stainless steel bushing is placed in a mold cavity that fits the bushing, and after pressing and forming, it is demolded to obtain a green blank.
[0013] The green blank is sintered and then subjected to solution treatment and aging to obtain the aluminum-steel composite cylinder liner.
[0014] In one embodiment, the silicon carbide reinforced aluminum matrix composite material raw material powder, by weight percentage, consists of 35% to 45% silicon carbide and the balance being aluminum alloy raw material powder.
[0015] In one embodiment, the aluminum alloy raw material powder, by weight percentage, consists of 3.1% zinc, 3.2% silicon, 4.2% magnesium, 1.5% copper, 0.5% cerium, 0.5% zirconium, and the balance aluminum.
[0016] In one embodiment, the amount of polyurethane added is 1% to 3% of the mass of the silicon carbide reinforced aluminum matrix composite raw material powder.
[0017] In one embodiment, the diameter of the millimeter hole is 0.1 mm to 0.3 mm, and the spacing between adjacent millimeter holes is 0.5 mm to 0.8 mm.
[0018] In one embodiment, the micro / nanopores are prepared by placing a 2Cr13 martensitic stainless steel bushing with millimeter-sized pores uniformly distributed on its surface in an electrolytic cell containing a perchloric acid solution for electrochemical etching; the current density of the electrochemical etching is 1.0 A / cm². 2 ~2.0A / cm 2 The time is 5 to 15 minutes.
[0019] In one embodiment, the pressing pressure is 50 MPa to 300 MPa.
[0020] In one embodiment, the sintering temperature is 580°C to 620°C.
[0021] In one embodiment, the solution treatment time is 4.5 to 6.5 hours and the temperature is 465°C to 480°C; the aging treatment time is 10 to 15 hours and the temperature is 160°C to 200°C.
[0022] In one embodiment, the process further includes mechanical shaping and anodizing of the aluminum-steel composite cylinder liner.
[0023] The above-mentioned method for preparing aluminum-steel composite cylinder liners involves filling a mold cavity adapted to the cylinder liner body with a mixed powder containing silicon carbide-reinforced aluminum-based composite material raw material powder, placing a stainless steel bushing in a mold cavity adapted to the bushing, and pressing it during the forming process. Under the action of extrusion pressure, the mixed powder enters the millimeter pores of the stainless steel bushing to form a tenon-and-mortise structure. Subsequently, during the sintering process, the alloying elements in the mixed powder form a liquid phase and enter the micro-nano pores of the stainless steel bushing, playing an anchoring role. After solution treatment and aging treatment, the resulting aluminum-steel composite cylinder liner has a strong bond between the silicon carbide-reinforced aluminum-based composite cylinder liner body and the stainless steel bushing. The stainless steel bushing ensures the high-temperature resistance of the friction surface, while the aluminum-based composite cylinder liner body ensures advantages such as light weight, high strength, and wear resistance. Detailed Implementation
[0024] To facilitate understanding of the present invention, a more comprehensive description is provided below, along with preferred embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0026] One embodiment of the method for preparing an aluminum-steel composite cylinder liner includes the following steps S110 to S170:
[0027] S110 provides silicon carbide reinforced aluminum matrix composite material powder.
[0028] In this embodiment, the silicon carbide reinforced aluminum matrix composite material raw material powder consists of 35% to 45% by mass of silicon carbide and the balance of aluminum alloy raw material powder (based on a total mass content of 100% for the silicon carbide reinforced aluminum matrix composite material raw material powder).
[0029] The aluminum alloy raw material powder consists of 3.1% zinc by mass, 3.2% silicon by mass, 4.2% magnesium by mass, 1.5% copper by mass, 0.5% cerium by mass, 0.5% zirconium by mass, and the balance aluminum (based on a total mass content of 100% for the aluminum alloy raw material powder).
[0030] Furthermore, the aluminum alloy raw material powder is composed of aluminum powder, aluminum-magnesium alloy powder (the magnesium content in the aluminum-magnesium alloy powder is 20%, denoted as Al-20%Mg), zinc powder, aluminum-silicon alloy powder (the silicon content in the aluminum-silicon alloy powder is 20%, denoted as Al-20%Si), aluminum-cerium alloy powder (denoted as Al-Ce), zirconium powder, and copper powder.
[0031] S120. Mix the above raw material powder with polyurethane evenly to obtain a mixed powder.
[0032] In this embodiment, the amount of polyurethane added is 1% to 3% of the mass of the raw material powder. Preferably, the amount of polyurethane added is 2% of the mass of the raw material powder.
[0033] Mixing the raw material powder with an appropriate amount of polyurethane can, on the one hand, utilize the excellent adhesion and bonding properties of polyurethane to enhance the adhesion between the raw material powders, making the mixed powder more uniform and stable; on the other hand, it can improve the flowability of the raw material powder, which is conducive to filling the mold and forming more smoothly.
[0034] S130 provides 2Cr13 martensitic stainless steel bushings with millimeter and micro / nano pores evenly distributed on the surface.
[0035] The diameter of the millimeter holes is 0.1 mm to 0.3 mm, and the spacing between adjacent millimeter holes is 0.5 mm to 0.8 mm. Preferably, the diameter of the millimeter holes is 0.2 mm, and the spacing between adjacent millimeter holes is 0.7 mm.
[0036] In this embodiment, the millimeter hole is prepared by the following method: after cleaning the 2Cr13 martensitic stainless steel bushing, it is immersed in a chemical etching solution, and the etching time and temperature are controlled to etch the location where the hole needs to be punched.
[0037] The chemical etching solution consists of ferric chloride (FeCl3), copper sulfate (CuSO4), and hydrogen peroxide (containing 20% hydrogen peroxide by mass). The etching time is 5–10 minutes, and the etching temperature is 35℃–45℃.
[0038] In this embodiment, the micro- and nanopores are prepared by the following method: a 2Cr13 martensitic stainless steel bushing with millimeter-sized pores on its surface is cleaned and placed in an electrolytic cell containing a perchloric acid solution, ensuring that it is correctly connected to the electrode. The etching current density and time are set as needed, and the electrolytic cell is started, allowing the chloride ions generated in the perchloric acid solution to undergo an oxidation-reduction reaction on the surface of the stainless steel plate, thereby forming micro- and nanopores on the stainless steel surface.
[0039] The current density is 1.0 A / cm². 2 ~2.0A / cm 2 The time is 5 to 15 minutes.
[0040] S140. A pressing die is provided, the die having a cavity adapted to the cylinder liner body and a cavity adapted to the bushing.
[0041] S150. The above-mentioned mixed powder is filled into the mold cavity that matches the cylinder liner body. The stainless steel bushing is placed in the mold cavity that matches the bushing. After pressing and forming, it is demolded to obtain a green blank.
[0042] In this embodiment, the pressing pressure is 50MPa to 300MPa.
[0043] During the pressing process, the mixed powder enters the millimeter holes on the surface of the stainless steel bushing under the action of extrusion pressure, forming a mortise and tenon structure.
[0044] S160. After sintering the above-mentioned green blanks, solution treatment and aging treatment are carried out to obtain aluminum-steel composite cylinder liners.
[0045] In this embodiment, the sintering temperature is 580℃~620℃. The solution treatment time is 4.5~6.5 hours, and the temperature is 465℃~480℃. The aging treatment time is 10~15 hours, and the temperature is 160℃~200℃.
[0046] By controlling the sintering temperature, the alloying elements in the mixed powder are liquefied and enter the micro- and nano-pores of the stainless steel bushing, thus playing an anchoring role.
[0047] S170. The above-mentioned aluminum-steel composite cylinder liner is mechanically shaped and anodized.
[0048] It is understandable that if the aluminum-steel composite cylinder liner that meets the requirements has been obtained in step S160, then step S170 can be omitted.
[0049] The following are specific examples.
[0050] Example 1
[0051] (1) Provide silicon carbide reinforced aluminum matrix composite material raw material powder, which is composed of 35% wt. silicon carbide and the balance aluminum alloy raw material powder;
[0052] (2) The above silicon carbide reinforced aluminum matrix composite material raw material powder is mixed with polyurethane to obtain a mixed powder;
[0053] (3) Provide 2Cr13 martensitic stainless steel bushings with millimeter and micro-nano pores evenly distributed on the surface.
[0054] (4) Provide a pressing mold having a mold cavity adapted to the cylinder liner body and a mold cavity adapted to the bushing;
[0055] (5) The above mixed powder is filled into a mold cavity that is compatible with the cylinder liner body, the stainless steel bushing is placed in a mold cavity that is compatible with the bushing, and after pressing and forming, it is demolded to obtain a green blank.
[0056] (6) After sintering the above-mentioned green blanks, solution treatment and aging treatment are carried out to obtain aluminum-steel composite cylinder liners.
[0057] Example 2
[0058] (1) Provide silicon carbide reinforced aluminum matrix composite material raw material powder, which is composed of 45% wt. silicon carbide and the balance aluminum alloy raw material powder, wherein the aluminum alloy raw material powder is composed of 3.1% wt. Zn, 3.2% wt. Si, 4.2% wt. Mg, 1.5% wt. Cu, 0.5% wt. Ce, 0.5% wt. Zr and the balance Al;
[0059] (2) The above silicon carbide reinforced aluminum matrix composite material raw material powder is mixed with polyurethane evenly, and the amount of polyurethane added is 1% of the raw material powder to obtain mixed powder.
[0060] (3) Provide 2Cr13 martensitic stainless steel bushings with millimeter and micro-nano pores evenly distributed on the surface.
[0061] (4) Provide a pressing mold having a mold cavity adapted to the cylinder liner body and a mold cavity adapted to the bushing;
[0062] (5) The above mixed powder is filled into a mold cavity that is compatible with the cylinder liner body, the stainless steel bushing is placed in a mold cavity that is compatible with the bushing, and after being pressed and formed by pressure of 50MPa, it is demolded to obtain a green blank.
[0063] (6) The above green blank is sintered at 580°C and then subjected to solution treatment and aging treatment. The solution treatment time is 4.5 hours and the temperature is 465°C. The aging treatment time is 10 hours and the temperature is 160°C to obtain aluminum-steel composite cylinder liner.
[0064] Example 3
[0065] (1) Provide silicon carbide reinforced aluminum matrix composite material raw material powder, which is composed of 40% wt. silicon carbide and the balance aluminum alloy raw material powder, wherein the aluminum alloy raw material powder is composed of 3.1% wt. Zn, 3.2% wt. Si, 4.2% wt. Mg, 1.5% wt. Cu, 0.5% wt. Ce, 0.5% wt. Zr and the balance Al;
[0066] (2) The above silicon carbide reinforced aluminum matrix composite material raw material powder is mixed with polyurethane evenly, and the amount of polyurethane added is 3% of the raw material powder to obtain mixed powder;
[0067] (3) A 2Cr13 martensitic stainless steel bushing with approximately 0.2 mm holes evenly distributed on its surface is provided. The stainless steel bushing is placed in an electrolytic cell containing perchloric acid solution for electrochemical etching. The current density of the electrochemical etching is 1.5 A / cm². 2 The time was 10 minutes, and a 2Cr13 martensitic stainless steel bushing with millimeter-sized and micro-nano pores evenly distributed on the surface was obtained.
[0068] (4) Provide a pressing mold having a mold cavity adapted to the cylinder liner body and a mold cavity adapted to the bushing;
[0069] (5) The above mixed powder is filled into a mold cavity that is compatible with the cylinder liner body, the stainless steel bushing is placed in a mold cavity that is compatible with the bushing, and after being pressed and formed by pressure of 300MPa, it is demolded to obtain a green blank.
[0070] (6) The above green blank is sintered at 620°C and then subjected to solution treatment and aging treatment, wherein the solution treatment time is 6.5 hours and the temperature is 480°C, the aging treatment time is 15 hours and the temperature is 200°C, to obtain aluminum-steel composite cylinder liner.
[0071] Example 4
[0072] (1) Provide silicon carbide reinforced aluminum matrix composite material raw material powder, which is composed of 40% wt. silicon carbide and the balance aluminum alloy raw material powder, wherein the aluminum alloy raw material powder is composed of 3.1% wt. Zn, 3.2% wt. Si, 4.2% wt. Mg, 1.5% wt. Cu, 0.5% wt. Ce, 0.5% wt. Zr and the balance Al;
[0073] (2) The above silicon carbide reinforced aluminum matrix composite material raw material powder is mixed with polyurethane evenly, and the amount of polyurethane added is 2% of the raw material powder to obtain mixed powder;
[0074] (3) A 2Cr13 martensitic stainless steel bushing with 0.3 mm holes evenly distributed on its surface is provided. The stainless steel bushing is placed in an electrolytic cell containing perchloric acid solution for electrochemical etching. The current density of the electrochemical etching is 2.0 A / cm². 2 The time was 5 minutes, and a 2Cr13 martensitic stainless steel bushing with millimeter and micro-nano pores evenly distributed on the surface was obtained.
[0075] (4) Provide a pressing mold having a mold cavity adapted to the cylinder liner body and a mold cavity adapted to the bushing;
[0076] (5) The above mixed powder is filled into a mold cavity that is compatible with the cylinder liner body, the stainless steel bushing is placed in a mold cavity that is compatible with the bushing, and after being pressed and formed by pressure of 200MPa, it is demolded to obtain a green blank.
[0077] (6) The above green blank is sintered at 600℃ and then subjected to solution treatment and aging treatment, wherein the solution treatment time is 6 hours and the temperature is 480℃, the aging treatment time is 12 hours and the temperature is 180℃, to obtain aluminum-steel composite cylinder liner.
[0078] Testing revealed that the aluminum-steel composite cylinder liners prepared in Examples 1-4 exhibited a strong bond between the cylinder liner body and the stainless steel bushing, and possessed excellent comprehensive properties such as lightweight, high strength, wear resistance, and high temperature resistance.
[0079] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing an aluminum-steel composite cylinder liner, characterized in that, Includes the following steps: Provides silicon carbide reinforced aluminum matrix composite material powder; The silicon carbide reinforced aluminum matrix composite material raw material powder is mixed evenly with polyurethane to obtain a mixed powder; Provide 2Cr13 martensitic stainless steel bushings with millimeter and micro / nano pores evenly distributed on the surface; A pressing mold is provided, the mold having a cavity adapted to the cylinder liner body and a cavity adapted to the bushing; The mixed powder is filled into a mold cavity that fits the cylinder liner body, the stainless steel bushing is placed in a mold cavity that fits the bushing, and after pressing and forming, it is demolded to obtain a green blank. The green blank is sintered and then subjected to solution and aging treatments to obtain the aluminum-steel composite cylinder liner. The diameter of the millimeter hole is 0.1mm to 0.3mm, and the spacing between adjacent millimeter holes is 0.5mm to 0.8mm; The micro- and nanopores are prepared by the following method: a 2Cr13 martensitic stainless steel bushing with millimeter-sized pores evenly distributed on its surface is placed in an electrolytic cell containing a perchloric acid solution and subjected to electrochemical etching; the current density of the electrochemical etching is 1.0 A / cm². 2 ~2.0A / cm 2 The time is 5 to 15 minutes.
2. The method for preparing the aluminum-steel composite cylinder liner according to claim 1, characterized in that, The silicon carbide reinforced aluminum matrix composite material raw material powder, by mass percentage, consists of 35% to 45% silicon carbide and the balance aluminum alloy raw material powder.
3. The method for preparing the aluminum-steel composite cylinder liner according to claim 2, characterized in that, The aluminum alloy raw material powder, by mass percentage, consists of 3.1% zinc, 3.2% silicon, 4.2% magnesium, 1.5% copper, 0.5% cerium, 0.5% zirconium, and the balance aluminum.
4. The method for preparing the aluminum-steel composite cylinder liner according to claim 1, characterized in that, The amount of polyurethane added is 1% to 3% of the mass of the silicon carbide reinforced aluminum matrix composite material powder.
5. The method for preparing the aluminum-steel composite cylinder liner according to any one of claims 1 to 4, characterized in that, The pressing pressure is 50MPa~300MPa.
6. The method for preparing the aluminum-steel composite cylinder liner according to any one of claims 1 to 4, characterized in that, The sintering temperature is 580℃~620℃.
7. The method for preparing the aluminum-steel composite cylinder liner according to any one of claims 1 to 4, characterized in that, The solution treatment time is 4.5 to 6.5 hours and the temperature is 465°C to 480°C; the aging treatment time is 10 to 15 hours and the temperature is 160°C to 200°C.
8. The method for preparing the aluminum-steel composite cylinder liner according to any one of claims 1 to 4, characterized in that, It also includes the steps of mechanical shaping and anodizing of the aluminum-steel composite cylinder liner.
Citation Information
Patent Citations
Sialon ceramic mud pump cylinder liner and producing method thereof
CN104696211A
Preparation method and application of aluminum-iron composite material for machine arm
CN112008084A